Sectional study of the occurrence of Bovine Viral Diarrhea Virus in pig farms in Sao Paulo State - Honorato Gatto, Igor Renan [UNESP]; Basso Cotrin, Jeferson Alaur [UNESP]; Souza Almeida, Henrique Meiroz de [UNESP]; Mechler, Marina Lopes [UNESP]; Oliveira, Luis Guilherme de [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2017)
Bovine Viral Diarrhea virus (BVDV) can infect pigs and lead to production losses. Data on the epidemiology of this virus in pigs are scarce. In order to obtain occurrence data of this disease, 600 blood serum samples of pigs from five farms in the northeast of the state of Sao Paulo were collected. Samples were divided into four categories: Weaning (W), Nursery (N), Finishing (F) and Sows (S), and were submitted to Virus neutralization (VN) test for BVDV-1 and BVDV-2. One (1/30) positive sample to BVDV-1 was detected in Property 2, showing 3.33% prevalence in (F) and a herd level prevalence of 0.84%. Regarding BVDV-2, in Property 2, 3.33% (1/30) of samples were seroreagent, obtained in (F) and 6.66% (2/30) in (S), with the herd prevalence of 2.44 %. Properties 3 and 4 presented, 3.33% (1/30) of seroreagent samples in the (S), with 0.84% at herd level, respectively. In Property 5, we found 6.66% (2/30) of seroreagent samples, both in (S), with a final prevalence of 1.66%. No risk factor was significantly associated. Despite the low prevalence, evidence of infection was found in different categories within the farms, showing that inefficiency in biosecurity can lead to infection in swine.
Keywords: BVDV-1; BVDV-2; Epidemiology; Swine; Virus neutralization